An Overview of Luminescent Bio-Based Composites - Pinto, Ricardo J. B.
The development of inorganic/organic composite materials represents a fast-growing interdisciplinary area in materials science and engineering. In this topic, a key idea is the production of composites comprising biopolymers and functional inorganic phases that could replace conventional materials in several high-technology applications. Following this concept, the use of different polymers from renewable sources, such as cellulose, starch, alginate, and chitosan, have gained great relevance because of their renewable nature, potential biocompatibility, and biodegradability, as well as specific physicochemical properties. The combination of these biopolymers with different fillers (including inorganic nanoparticles (NPs), clusters, or ions) allows the design of innovative bio-based materials with specific and/or improved properties, namely, optical, mechanical, and barrier properties, luminescence, and biological properties (as antimicrobial activity and biocompatibility). This review will focus on the most important synthetic approaches, properties, and applications of luminescent bio-based composites obtained by combining different biopolymers and fillers. (C) 2014 Wiley Periodicals, Inc.